(untitled) ("Journal "U". Economy. Management. Finance.", 2018)
This article provides an analysis of the current situation on the cryptocurrency market, provides forecasts for its development in 2019. The current leaders are considered and the advantages necessary for the new digital money to conquer the cryptocurrency market are revealed.